Transcatheter Aortic Valve Replacement in Young Low-Risk Patients With Severe Aortic Stenosis: A Review - Bocchino, Pier Paolo; Angelini, Filippo; Alushi, Brunilda; Conrotto, Federico; Cioffi, Giacomo Maria; Tersalvi, Gregorio; Senatore, Gaetano; Pedrazzini, Giovanni; De Ferrari, Gaetano Maria; Biasco, Luigi (Frontiers in Cardiovascular Medicine, 2020)
In the last decades, transcatheter aortic valve replacement (TAVR) revolutionized the treatment of symptomatic severe aortic stenosis. The efficacy and safety of TAVR were first proven in inoperable and high-risk patients. Then, subsequent randomized clinical trials showed non-inferiority of TAVR as compared to surgical aortic valve replacement also in intermediate- and low-risk populations. As TAVR was progressively studied and clinically used in lower-risk patients, issues were raised questioning its opportunity in a younger population with a longer life-expectancy. As long-term follow-up data mainly derive from old studies with early generation devices on high or intermediate surgical risk patients, results can hardly be extended to most of currently treated patients who often show a low surgical risk and are treated with newer generation prostheses. Thus, in this low-risk younger population, decision making is difficult due to the lack of supporting data. The aim of the present review is to revise current literature regarding TAVR in younger patients.